The 1.2 km shuttle run test: Reliability and comparison with the Yo-Yo Intermittent Recovery Level 1 Test in young elite rugby union players - Deuchrass, R. W.; Smith1, H. K.; Elliot, C. E.; Lizamore, C. E.; Hamlin, M. J. (Journal of Australian Strength and Conditioning, 2019)
The 1.2SRT was a moderately reliable test of intermittent running performance in rugby players with a coefficient of variation (CV) of 2.4% between tests, while also showing high association (validity) with the Yo-Yo IRT L1 (r = -0.87).